2021
DOI: 10.1172/jci.insight.140669
|View full text |Cite
|
Sign up to set email alerts
|

Tristetraprolin expression by keratinocytes protects against skin carcinogenesis

Abstract: Cancer is caused primarily by genomic alterations resulting in deregulation of gene regulatory circuits in key growth, apoptosis or DNA repair pathways. Multiple genes associated with the initiation and development of tumors are also regulated at the level of mRNA decay, through the recruitment of RNA binding proteins to AU-rich elements (AREs) located in their 3'untranslated regions. One of these ARE-binding proteins, tristetraprolin (TTP, encoded by Zfp36) is consistently dysregulated in many human malignanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…28 However, TTPDARE mice are resistant to experimental models of imiquimod-induced dermatitis, collagen antibody-induced arthritis, experimental autoimmune encephalomyelitis, bacterial gingivitis and dental bone erosion, inflammatory lung damage, experimental autoimmune uveitis, and chemically induced skin carcinogenesis. [29][30][31][32] We previously showed that glucocorticoids are master regulators of gastric inflammation. Systemic removal of endogenous glucocorticoids by ADX triggers massive, spontaneous gastric inflammation and SPEM.…”
mentioning
confidence: 99%
“…28 However, TTPDARE mice are resistant to experimental models of imiquimod-induced dermatitis, collagen antibody-induced arthritis, experimental autoimmune encephalomyelitis, bacterial gingivitis and dental bone erosion, inflammatory lung damage, experimental autoimmune uveitis, and chemically induced skin carcinogenesis. [29][30][31][32] We previously showed that glucocorticoids are master regulators of gastric inflammation. Systemic removal of endogenous glucocorticoids by ADX triggers massive, spontaneous gastric inflammation and SPEM.…”
mentioning
confidence: 99%
“…These 3 markers, KRT5, KRT6A, and APOE, are part of a tight correlation network (Figure 4E and Supplementary Figure 3) that includes other genes and whose expression levels track with SSc severity and are involved in a range of functional processes. ZFP36 encodes tristetraprolin, an AU‐rich element RNA binding protein that is up‐regulated in wounded skin and controls inflammatory cytokines as well as neoplastic processes in keratinocytes (18,19). S100A2 regulates keratinocyte differentiation through its interaction with p53 (20), and expression of the alarmin S100A8 is associated with increased keratinocyte proliferation and epithelial–mesenchymal transition (21).…”
Section: Resultsmentioning
confidence: 99%
“…These findings support the potential benefit of targeting chemotherapy-induced senescent cells as a strategy to reduce occurrence of second cancer in the future. A recent study demonstrated that RNA-binding protein tristetraprolin that binds to AU-rich elements (AREs) in the 3′-untranslated regions of mRNAs and targets ARE-containing mRNAs for degradation, is an important regulator of skin carcinogenesis and may represent a useful therapeutic target ( 219 ). Of note, the critical role of the interleukin (IL)-33/regulatory T cell (Treg) axis in chronic inflammation-induced tumor-promoting environment both in the skin and colon has been recently elucidated, suggesting a promising therapeutic strategy for the treatment and prevention of cancers associated with chronic inflammation ( 220 ).…”
Section: In Vivo Modelsmentioning
confidence: 99%